Design of a General‐Purpose European Compound Screening Library for EU‐OPENSCREEN. Issue 10 (15th July 2014) - Horvath, Dragos; Lisurek, Michael; Rupp, Bernd; Kühne, Ronald; Specker, Edgar; von Kries, Jens; Rognan, Didier; Andersson, C. David; Almqvist, Fredrik; Elofsson, Mikael; Enqvist, Per‐Anders; Gustavsson, Anna‐Lena; et al.
Abstract This work describes a collaborative effort to define and apply a protocol for the rational selection of a general‐purpose screening library, to be used by the screening platforms affiliated with the EU‐OPENSCREEN initiative. It is designed as a standard source of compounds for primary screening against novel biological targets, at the request of research partners. Given the general nature of the potential applications of this compound collection, the focus of the selection strategy lies on ensuring chemical stability, absence of reactive compounds, screening‐compliant physicochemical properties, loose compliance to drug‐likeness criteria (as drug design is a major, but not exclusive application), and maximal diversity/coverage of chemical space, aimed at providing hits for a wide spectrum of drugable targets. Finally, practical availability/cost issues cannot be avoided. The main goal of this publication is to inform potential future users of this library about its conception, sources, and characteristics. The outline of the selection procedure, notably of the filtering rules designed by a large committee of European medicinal chemists and chemoinformaticians, may be of general methodological interest for the screening/medicinal chemistry community. The selection task of 200K molecules out of a pre‐filtered set of 1.4M candidates was shared by five independent European research groups, each picking a subset of 40K compounds according to their own in‐house methodology and expertise. An in‐depth analysis of chemical space coverage of the library serves not only to characterize the collection, but also to compare the various chemoinformatics‐driven selection procedures of maximal diversity sets. Compound selections contributed by various participating groups were mapped onto general‐purpose self‐organizing maps (SOMs) built on the basis of marketed drugs and bioactive reference molecules. In this way, the occupancy of chemical space by the EU‐OPENSCREEN library could be directly compared with distributions of known bioactives of various classes. This mapping highlights the relevance of the selection and shows how the consensus reached by merging the five different 40K selections contributes to achieve this relevance. The approach also allows one to readily identify subsets of target‐ or target‐class‐oriented compounds from the EU‐OPENSCREEN library to suit the needs of the diverse range of potential users. The final EU‐OPENSCREEN library, assembled by merging five independent selections of 40K compounds from various expert groups, represents an excellent example of a Europe‐wide collaborative effort toward the common objective of building best‐in‐class European open screening platforms.